2013
DOI: 10.1007/s10162-013-0431-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Metformin Against Cisplatin-Induced Ototoxicity in an Auditory Cell Line

Abstract: Metformin, an antidiabetic drug with potent anticancer activity, is known to prevent oxidative stress-induced cell death in several cell types through a mechanism dependent on the mitochondria. In the present study, we investigated the influence of metformin on cisplatin ototoxicity in an auditory cell line. Cell viability was determined using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide (Sigma, St. Louis, MO, USA) cell proliferation assay. Oxidative stress and apoptosis were assessed by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 37 publications
0
37
1
Order By: Relevance
“…Other agents interfere only with the ototoxicity of cisplatin, including Gingko biloba [42], ebselen (a synthetic compound with an activity similar to that of glutathione peroxidase) [43], and amifostine [24]. Other protective compounds, whose antineoplastic effects have not been evaluated, include metformin [3] and silymarin, a lipophilic extract derived from the plant Silybum marianum [23]. A suggestion made by some studies is the application of protective agents such as D -methionine and N -acetylcysteine directly to the eardrum or via the round window to abolish the interference with the systemic toxicity induced by cisplatin [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other agents interfere only with the ototoxicity of cisplatin, including Gingko biloba [42], ebselen (a synthetic compound with an activity similar to that of glutathione peroxidase) [43], and amifostine [24]. Other protective compounds, whose antineoplastic effects have not been evaluated, include metformin [3] and silymarin, a lipophilic extract derived from the plant Silybum marianum [23]. A suggestion made by some studies is the application of protective agents such as D -methionine and N -acetylcysteine directly to the eardrum or via the round window to abolish the interference with the systemic toxicity induced by cisplatin [13].…”
Section: Discussionmentioning
confidence: 99%
“…This kind of toxicity can interfere with drug treatment in many patients by necessitating decreases in the dosage, frequency, and duration of chemotherapy [2]. There is no cure or preventive treatment of ototoxicity in these patients [3]. This effect was first described by Rossof and has been widely studied since then [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin has been demonstrated to act synergistically with DDP to decrease tumor size and inhibit angiogenesis in mice, indicating that it could bea reasonable candidate for combination with DDP-dependent therapy (3). However, a previous study found that metformin antagonizes the DDP-dependent apoptotic effect by suppressing oxidative stress and inhibiting the caspase-dependent activation of apoptosis in certain cancer cells (14). The present study examined the combination of metformin and DDP as a novel treatment for ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al [2011] observed that metformin protects an auditory cell line against gentamicin-induced apoptosis. Recently, Chang et al [2014] showed that metformin had a protective effect against cisplatin-induced ototoxicity in an auditory cell line. These studies did not consider HCs or SGNs from cochlear tissue.…”
Section: Introductionmentioning
confidence: 99%